The perfect database round-trip using JAXB and JDO. - Zade, Rajesh (XML journal :the ultimate enterprise resource.)
Java Data Objects (JDO) enables Java developers to perform database transactions from within Java objects without writing database (SQL) or JDBC-specific code. Java Architecture for XML Binding (JAXB) and JDO provide great APIs for performing complex XML and database oriented tasks. But what about using the two in tandem? This article is about combining these technologies to solve the complex tasks of data access and data persistence.